Bones. The complete sixth season [videorecording (DVD)] - Hanson, Hart (Bones, 2011)
After a much-needed break, forensic anthropologist Dr. Temperance Brennan and FBI Special Agent Seeley Booth return to the Jeffersonian Institute, along with their team of investigative 'squints, ' for another darkly humorous season of murder, mystery, controversy and chemistry. In addition to a vast array of personal crises, ranging from Angela's secret pregnancy to Booth's new relationship with a beautiful reporter, the team tackles a complex caseload of gruesome crimes.